Cobalt‐Catalyzed Intramolecular Hydroacylation Involving Cyclopropane Cleavage. Issue 37 (17th June 2020) - Yang, Junfeng; Mori, Yuto; Yamanaka, Masahiro; Yoshikai, Naohiko
Abstract: A simple cobalt‐diphosphine catalyst has been found to efficiently promote intramolecular cyclization of ortho ‐cyclopropylvinyl‐ and cyclopropylidenemethyl‐substituted benzaldehydes into benzocyclooctadienone and benzocycloheptadienone derivatives, respectively. This ring‐opening hydroacylation likely involves aldehyde C−H oxidative addition, olefin insertion, cyclopropane cleavage by β‐carbon elimination, and C−C bond‐forming reductive elimination, as was supported by mechanistic experiments and DFT calculations. Abstract : A simple cobalt‐diphosphine catalyst efficiently promotes intramolecular ring‐opening hydroacylation of vinylcyclopropane and alkylidenecyclopropane to afford eight‐ and seven‐membered carbocyclic products. The reaction likely proceeds via C−H oxidative addition, olefin insertion, β‐carbon elimination, and C−C reductive elimination as key steps, as was supported by mechanistic experiments and DFT calculations (see scheme).